PENGGUNAAN TEORI BIAYA TRANSAKSI DALAM PERILAKU PEMBELIAN ONLINE - Maria Augustin Lopes Amaral; Maria B. M. G. Wutun (FEB Universitas Sam Ratulangi Manado, 2022)
Abstract: The purpose of this research is to prove and analyze the effect of uncertainty variable, trust and frequency buying on transaction cost economics, as well as the implications of transaction cost economics on consumer's willingness to buy online. The sample is 115 people. The data comes from analyzed with SEM AMOS version 24. The results showed that the brand uncertainty of online stores had no effect on transaction cost economics. Meanwhile, performance uncertainty of products has a positive effect on transaction cost economics. Dependability of online store, privacy policy and buying frequency have a negative effect on transaction cost economics. Transaction cost economics has a negative effect on consumer's willingness to buy online.Abstrak: Tujuan peneltian yaitu membuktikan dan menganalisis pengaruh variabel uncertainty, trust dan frequency buying terhadap transaction cost economics, serta implikasi transaction cost economics terhadap consumer’s willingness to buy online. Banyaknya responden di penelitian ini adalah 115 orang. Perolehan data dianalisis dengan menggunakan SEM AMOS versi 24. Hasil penelitian menunjukkan bahwa brand uncertainty of online stores tidak berpengaruh terhadap transaction cost economics. Sedangkan performance uncertainty of products berpengaruh positif terhadap transaction cost economics. Dependability of online store, privacy policy dan buying frequency berpengaruh negatif terhadap transaction cost economics. Transaction cost economics berpengaruh negatif terhadap consumer’s willingness to buy online